2010
DOI: 10.1002/biof.111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol and flavonols on cardiovascular function: Physiological mechanisms

Abstract: Resveratrol and flavonols are commonly found together in fruits and vegetables and, therefore, consumed in the diet. These two polyphenols share both vasorelaxant and antioxidant activity and may act together to improve cardiovascular function. This review examines the mechanisms by which resveratrol and flavonols influence cardiovascular function and perhaps offer a new approach for the development of therapeutic agents for the prevention and/or treatment of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 108 publications
1
12
0
1
Order By: Relevance
“…Recently, the ethanolic extract of this plant, which is known to contain a variety of flavones (Yenjai et al, 2004), has been shown to inhibit phenylephrineinduced contractile responses of the rat aorta (Wattanapitayakul et al, 2008), increase blood flow to the testis (Chaturapanich et al, 2008) and enhance nitric oxide (NO) production in human umbilical vein endothelial cells . These actions are consistent with the reported vascular and antioxidant actions of flavones (Woodman and Chan, 2004;Yap et al, 2010). The compounds showing NO production can be promising candidates for vasodilation, which may serve as an effective anti-ischaemia agent to adjust blood flow to normal, and finally recover dysfunction of heart induced by ischaemia.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, the ethanolic extract of this plant, which is known to contain a variety of flavones (Yenjai et al, 2004), has been shown to inhibit phenylephrineinduced contractile responses of the rat aorta (Wattanapitayakul et al, 2008), increase blood flow to the testis (Chaturapanich et al, 2008) and enhance nitric oxide (NO) production in human umbilical vein endothelial cells . These actions are consistent with the reported vascular and antioxidant actions of flavones (Woodman and Chan, 2004;Yap et al, 2010). The compounds showing NO production can be promising candidates for vasodilation, which may serve as an effective anti-ischaemia agent to adjust blood flow to normal, and finally recover dysfunction of heart induced by ischaemia.…”
Section: Introductionsupporting
confidence: 86%
“…Therefore the first aim of the present study was to investigate the mechanisms of action of KPE in causing vasorelaxation in rat isolated thoracic aorta, in particular the involvement of calcium and endothelium-derived NO. The second aim of the study was to determined whether KPE reduces superoxide generation in rat aortae and protects endothelium-dependent relaxation of rat aorta against oxidative stress as previously reported for flavones and flavonols (Woodman and Chan, 2004;Yap et al, 2010). Finally, the positive outcomes from those investigations then led us to determine whether KPE was able to attenuate cardiac dysfunction resulting from global ischaemia and reperfusion of the rat isolated heart.…”
Section: Introductionmentioning
confidence: 95%
“…In addition to questions about the practical utility of such a term, the theoretical basis for assessing the impact of “total” flavonoid intakes on cardiovascular disease is also uncertain. Although there are many putative biological mechanisms underlying a possible cardioprotective role for flavonoids, 113,114 including antioxidant, 16,115,116 vasodilatory, 117–123 antithrombotic, 23,124–127 anti‐inflammatory, 19,21,22,48,128 and endothelial protective 23,35,48,129,130 properties of some of the compounds, 131 the effects of the flavonoids appear to vary from compound to compound within each class, rather than being inherent in all compounds in each of the several classes 1,50 …”
Section: Discussionmentioning
confidence: 99%
“…They exhibit a variety of biological actions such as antithrombotic, anti-inflammatory, antioxidant and vasorelaxant effects [14], [15]. There is growing evidence that consumption of a flavonoid-rich diet reduces the risk of cardiovascular disease states associated with overproduction of ROS [16], [17].…”
Section: Introductionmentioning
confidence: 99%